Which service is better on a linear travel corridor: Park & ride or on-demand public bus?. (December 2018) - Zhang, Jie; Wang, David Z.W.; Meng, Meng
Abstract: This paper develops an analytical model to support the decision-making for selection of a public transport service (PTS) provision between park & ride and on-demand public bus (ODPB). The objective of the model is to maximise the total social welfare, which includes consumer surplus and operator's net profit. The model is solved by a heuristic solution procedure and tested on an idealized linear travel corridor. The case study considers the effects from population density, density distribution, size of residential area, P&R station location, distance from the residential area to centre business area (CBD), as well as the changes of residential area layout and population growth. Results show that P&R fits for low population density area while ODPB is more suitable for high population density area. Population distribution type has little influence on the services' social welfare. ODPB is a preferable service for the city which does not have advanced metro network. Besides, the investment time for building ODPB service in the planning horizon is discussed with consideration of the development of residential area.